Preliminary findings of cerebral responses on transcutaneous vagal nerve stimulation on experimental heat pain - Usichenko, Taras; Laqua, René; Leutzow, Bianca; Lotze, Martin (Brain imaging and behavior, 2017)
Transcutaneous vagal nerve stimulation (TVNS) is a promising complementary method of pain relief. However, the neural networks associated with its analgesic effects are still to be elucidated. Therefore, we conducted two functional magnetic resonance imaging (fMRI) sessions, in a randomized order, with twenty healthy subjects who were exposed to experimental heat pain stimulation applied to the right forearm using a Contact Heat-Evoked Potential Stimulator. While in one session TVNS was administered bilaterally to the concha auriculae with maximal, non-painful intensity, the stimulation device was switched off in the other session (placebo condition). Pain thresholds were measured before and after each session. Heat stimulation elicited fMRI activation in cerebral pain processing regions. Activation magnitude in the secondary somatosensory cortex, posterior insula, anterior cingulate and caudate nucleus was associated with heat stimulation without TVNS. During TVNS, this association was only seen for the right anterior insula. TVNS decreased fMRI signals in the anterior cingulate cortex in comparison with the placebo condition; however, there was no relevant pain reducing effect over the group as a whole. In contrast, TVNS compared to the placebo condition showed an increased activation in the primary motor cortex, contralateral to the site of heat stimulation, and in the right amygdala. In conclusion, in the protocol used here, TVNS specifically modulated the cerebral response to heat pain, without having a direct effect on pain thresholds.